2012
DOI: 10.1002/chem.201201943
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Mechanism of the Arylsulfatase Promiscuous Enzyme from Pseudomonas Aeruginosa

Abstract: To elucidate the working mechanism of the "broad substrate specificity" by the Pseudomonas aeruginosa aryl sulfatase (PAS) enzyme, we present here a full quantum chemical study performed at the density functional level. This enzyme is able to catalyze the hydrolysis of the original p-nitrophenyl-sulfate (PNPS) substrate and the promiscuous p-nitrophenyl-phosphate (PNPP) one with comparable reaction kinetics. Based on the obtained results, a multistep mechanism including activation of the nucleophile, the nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 111 publications
0
48
0
Order By: Relevance
“…The reliability of cluster model in enzymatic catalysis has been largely explored in the last decades by different groups and for a huge number of enzymes …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability of cluster model in enzymatic catalysis has been largely explored in the last decades by different groups and for a huge number of enzymes …”
Section: Resultsmentioning
confidence: 99%
“…The considered Asp and Glu residues are modelled by a CH 3 COO − group, the Ser169 by CH 3 OH, the Asn256 by CH 3 CONH 2 and the arginine residues by CH 3 NH(NH 2 ) 2 + as it can be evinced by Figure . Following the standard procedure in the modelling enzymes with the cluster approach to keep the optimized structures resembling the experimental one, the truncation atoms except those of PQQ and metal‐coordinated amino acids, have been fixed at their crystallographic positions during the geometries optimization. The final model consists of 113 atoms, including the substrate (CH 3 OH) and has a total charge of zero.…”
Section: Computational Detailsmentioning
confidence: 99%
“…A recent theoretical study has suggested that the initial nucleophilic attack of fGly-diol on substrate may be rate-determining, and not the subsequent elimination. 35 Perhaps inconsistent with this prediction, a measured β LG of 0 for V max but −0.86 for V max / K M for PAS suggests that the alkoxide leaving group is not involved in the rate-determining step but only the first irreversible chemical step. 36 For the desulfation step, hydrolysis of the sulfoenzyme intermediate by water in the S N 2 pathway may be quite slow compared to E2, again for the reason for S-O bond cleavage.…”
Section: Fgly Participates Directly In Sulfate Ester Hydrolysismentioning
confidence: 95%
“…Here, the preferred mechanism appears instead to be one in which a nearby (more basic) histidine is utilized as a general base to activate the nucleophile. 21 We also explored the suggestion that a metal-coordinated Asp adjacent to the nucleophile can act as a base, 157,161 but found this mechanism to have very unfavorable energetics, perhaps unsurprisingly in light of the low p K a of a metal-bound aspartate, as well as the fact that this residue plays a clear structural role and protonating it will be detrimental to the stability of the metal coordination. Additionally, we found no need for acid catalysis to protonate the departing leaving group, however, in this particular case, one is dealing with a very good leaving group ( p -nitrophenol) and this may not be the case for more basic leaving groups such as e.g.…”
Section: Examples Of Recent Computational Studiesmentioning
confidence: 99%